Peran dan Fungsi Perbankan Syariah Perspektif Sosio-Kultur - Subaidi Subaidi (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
In the context of urban economic community of Indonesia, several terms, such as paroan, prapatan, dan pertelon are quite popular. Such terminology has influence economic activities which have become tradition that support profit sharing principles which are practiced by Sharia banking. Such profit sharing practices basically aims creating justice and provide balances for economic users and their environments. Furthermore, profit sharing practices show partnership relation among enterprise practitioners; more than just the relationship between superiors and subordinators. These kinds of spirits not only end in profit orientedd but also establish human based on relationship which aims at helping and caring either. Dealing with the nature of the sprit above, Sharia economic practitioners should have energized and inspired, abled to realize them in more reality, and was synergic economic relationship. However, one important thing that they usually forget to develop business institution is lack of understanding toward the culture of the society local culture and wisdom of the society is one of the significant factors required in designing, harmonizing, and, developing business. This implies that a where they built business, including Sharia banking. Understanding toward business institution should not aim at corporate oriented only. In fact, it should have relations of socio-culture and corporate social responsibility.